Subchronic exposure to titanium dioxide nanoparticles modifies cardiac structure and performance in spontaneously hypertensive rats - Rossi, Stefano; Savi, Monia; Mazzola, Marta; Pinelli, Silvana; Alinovi, Rossella; Gennaccaro, Laura; Pagliaro, Alessandra; Meraviglia, Viviana; Galetti, Maricla; Lozano-Garcia, Omar; Rossini, Alessandra; Frati, Caterina; et al. (Particle and fibre toxicology, 2019)
Non-communicable diseases, intended as the results of a combination of inherited, environmental and biological factors, kill 40 million people each year, equivalent to roughly 70% of all premature deaths globally. The possibility that manufactured nanoparticles (NPs) may affect cardiac performance, has led to recognize NPs-exposure not only as a major Public Health concern, but also as an occupational hazard. In volunteers, NPs-exposure is problematic to quantify. We recently found that inhaled titanium dioxide NPs, one of the most produced engineered nanomaterials, acutely increased cardiac excitability and promoted arrhythmogenesis in normotensive rats by a direct interaction with cardiac cells. We hypothesized that such scenario can be exacerbated by latent cardiovascular disorders such as hypertension. We monitored cardiac electromechanical performance in spontaneously hypertensive rats (SHRs) exposed to titanium dioxide NPs for 6 weeks using a combination of cardiac functional measurements associated with toxicological, immunological, physical and genetic assays. Longitudinal radio-telemetry ECG recordings and multiple-lead epicardial potential mapping revealed that atrial activation times significantly increased as well as proneness to arrhythmia. At the third week of nanoparticles administration, the lung and cardiac tissue encountered a maladaptive irreversible structural remodelling starting with increased pro-inflammatory cytokines levels and lipid peroxidation, resulting in upregulation of the main pro-fibrotic cardiac genes. At the end of the exposure, the majority of spontaneous arrhythmic events terminated, while cardiac hemodynamic deteriorated and a significant accumulation of fibrotic tissue occurred as compared to control untreated SHRs. Titanium dioxide nanoparticles were quantified in the heart tissue although without definite accumulation as revealed by particle-induced X-ray emission and ultrastructural analysis. The co-morbidity of hypertension and inhaled nanoparticles induces irreversible hemodynamic impairment associated with cardiac structural damage potentially leading to heart failure. The time-dependence of exposure indicates a non-return point that needs to be taken into account in hypertensive subjects daily exposed to nanoparticles.